Study of the predictive value of testosterone in androgen deprivation therapy for metastatic hormone-sensitive prostate cancer—the dual clinical research center for western and eastern China - Ma, Dongsheng; Zhang, Xiaoguang; Xi, Jianhong (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to investigate the association between early testosterone (T) response to androgen deprivation therapy (ADT) and clinical outcomes in metastatic hormone-sensitive prostate cancer (mHSPC).MethodsThis retrospective cohort study analyzed 366 mHSPC patients treated at The People’s Hospital Bozhou and The First Affiliated Hospital of Xinjiang Medical University. The participants were stratified by 1-month testosterone response: response group (T < 50 ng/dL) and non-response group (T > 50 ng/dL). The response group was further subdivided into ultra-low (T < 20 ng/dL) and low (20–50 ng/dL) response groups. Comparative analyses of baseline characteristics, progression to metastatic castration-resistant prostate cancer (mCRPC), and survival outcomes were carried out.ResultsNo significant intergroup differences were observed in Gleason score, tumor stage, prostate volume, initial PSA, PSA density, perineural invasion, visceral metastasis, or hazard level (all P > 0.05). However, the T non-response group exhibited a higher tumor load prevalence (76.77% vs. 60.10%, P = 0.004). The T non-response group demonstrated shorter mCRPC progression time (13.38 ± 8.88 vs. 20.40 ± 11.91 months, P < 0.001), though no difference emerged between the T ultra-low and low response subgroups (20.59 ± 11.91 vs. 20.86 ± 12.19 months, P = 0.876). Survival analysis revealed superior 3-year survival in T responders (P = 0.024), with T ultra-low responders showing significant advantages in both overall survival (P = 0.010) and 3-year survival (P = 0.001) compared to T low responders.ConclusionUltra-low T levels (<20 ng/dL) after 1-month ADT can be used as a reference standard for predicting survival outcomes and may guide treatment optimization in mHSPC.